PENERAPAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA PESERTA DIDIK KELAS IV SD N CIWAKTU - Fazri Yulianto; Nana Hendracipta; Lili Fajrudin; Lucyana Lucyana (LPPM Universitas Bina Bangsa, 2023)
In efforts to improve student learning outcomes, the teacher must improve the learning process carried out. One of the efforts that teachers can make in improving the learning process to be able to improve student learning outcomes is by applying the Team Assisted Individualization (TAI) learning model. The Team Assisted Individualization (TAI) learning model is an effort to improve the learning process because this learning model emphasizes guidance between group members to understand and solve the problems being studied. This research is a Classroom Action Research (CAR) which aims to improve the learning process so that it can improve student learning outcomes. This Classroom Action Research was conducted in class IV of SD N Ciwaktu in science learning. The results showed that the learning completeness in the pre-cycle was 42.85% of the total number of students. In cycle I the learning outcomes of students increased by 17.86% and the level of completeness of student learning outcomes in cycle I reached 60.71%. Whereas in cycle II the percentage of completeness of student learning outcomes obtained reached 89.28% with the frequency of students completing in cycle II as many as 25 students. Based on the results of the study, it was concluded that the application of the Team Assisted Individualization (TAI) model could improve the learning outcomes of fourth-grade students at SD N Ciwaktu in the Science subject.